Funding of Higher Education in Lithuania in the Context of Foreign Experience - Šileika, Algis; Tamašauskienė, Zita (Ekonomika, 2005)
During the last decade, a significant development of higher education in Western Europe (WE) and OECD countries took place, particularly in Lithuania. The general number of tertiary students increased up to 2.9 times within the period 1996-2003. However, at the same time funding per student significantly decreased. The article addresses private and public higher education benefits and states that to ensure additional periodic funding of higher education it is necessary to target more to the new funding mechanisms which allow for different process participants to share in a more efficient way the educational costs and benefits. Advantages and deficiencies of different types (models) of loans used by students in foreign countries are provided, stating that the greatest number of advantages when funding investments to higher education is found in income-contingent loans. In the opinion of the authors, in order to increase the funding of higher education we should refer more to students’ payments for studies, at the same time increasing financial support for students when granting loans and providing the opportunities for all students to get such support.